Mathematics for business, finance, and economics - Wilkes, F. M. (International Thomson Business Press, 1999)
This book is about: Straight lines and linear equations; Linear inequalities; Matrices; Functions and turning points; Derivatives and optimization; Functions of than one variable; ...